HUBUNGAN POLA ASUH ORANG TUA DENGAN KENAKALAN REMAJA - Harfendo Nugroho; Joko Pitoyo; Rahmawati Maulidia (STIKes Maharani Malang, 2022)
Introduction : Adolescence is a very important period in the process of growth and development of children, this period must first be in adolescence becaouse adolescence can not make moral deviations and the past that can damage the past alone. The role of parents becomes very important in caring for children, by using proper parenting. Method: This type of research is a comparison of literature using the literature method using literature using Google Scolar database and NEJM, org for previous research using desaig, cross-sectional, quantitative qualitative, analysis and descriptive published from 2015-2020. This literature is reviewed based on published titles, abstracts, complete texts and starts that begin for the feasibility of the study then tabulates data and narrative analysis. Results and Analysis: based on searches on google scholar and NEJM.org using the keywords parenting style, juvenile delinquency, obtained as many as 12 journals. From the google scholar 6 database and from the NEJM.org database, the are 6 journals. Discussion : the most common pattern of parenting done by parents to care for children is the pattern of pemisif care and outoritative while the pattern of outgiving is rarely performed by parents to care for their children. Some factors of delinqueny in adolescents are environmental factors, gender, age, children with broken home, and the most influencing factors are parenting style. Keywords: Juvenile delinquency, Parenting